Cutis verticis gyrata in a Patient with Familial presenile sebaceous hyperplasia Presenting as “Leonine facies”: A Rare Case - Sutedja EK; Sutedja E; Ruchiatan K; Faldian Y; Yogya Y; Dwiyana RF; Maharani RH; Budiarsa M (Clinical, Cosmetic and Investigational Dermatology, 2025)
Eva Krishna Sutedja, Endang Sutedja, Kartika Ruchiatan, Yogi Faldian, Yuri Yogya, Reiva Farah Dwiyana, Retno Hesty Maharani, Marshel Budiarsa Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran - Dr. Hasan Sadikin Hospital, Bandung, West Java, IndonesiaCorrespondence: Eva Krishna Sutedja, Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran - Dr. Hasan Sadikin Hospital, Jl. Pasteur 38, Bandung, West Java, Indonesia, Tel +628122014300 ext. 3449, Fax +62222032426, Email eva.krishna@unpad.ac.idAbstract: Cutis verticis gyrata (CVG) is a rare dermatological disorder characterized by thickened, gyriform folds and ridges of the skin, predominantly affecting the head and face. Based on etiology, it is classified into primary and secondary forms. Familial presenile sebaceous hyperplasia (FPSH), a rare variant of sebaceous hyperplasia, follows an autosomal dominant inheritance pattern with incomplete penetrance and variable severity among family members. We report a case of a 60-year-old male who presented to the Dermatology and Venereology Department, Hasan Sadikin General Hospital, Bandung, with thick plaques and deep furrows on the forehead, giving a “leonine facies” appearance. These lesions first appeared 25 years ago and progressively increased in number and spread to the neck and chest. Similar symptoms were observed in his twin brother and son. Investigations including skin slit smears, blood tests, serum biochemistry, imaging, and testosterone levels were unremarkable. Histopathological examination of facial papules and nodules showed enlarged sebaceous glands in the dermis, supporting the diagnosis of sebaceous hyperplasia. The patient was diagnosed with FPSH associated with CVG. Although rare, both conditions may be linked to systemic abnormalities, highlighting the importance of comprehensive evaluation. There is no definitive treatment for FPSH or CVG; current management is mainly cosmetic. Isotretinoin, with its sebocyte-suppressing effect, may reduce gland size but has a high recurrence rate upon discontinuation. Early recognition and a multidisciplinary approach are crucial to prevent further progression, particularly in older patients.Keywords: cutis verticis gyrata, familial presenile sebaceous hyperplasia, leonine facies